Association between Bisphenol A exposure and body composition parameters in children - Guo, Yong; Liu, Cui; Deng, Yu-Hong; Ning, Jing; Yu, Li; Wu, Jie-Ling (Frontiers in Endocrinology, 2023)
Background: Although there is evidence linking Bisphenol A (BPA) exposure to obesity, research examining its relationship with body composition parameters in young children is limited. Methods: A cross-sectional investigation was conducted on 200 preschool children aged between 4 and 6 years in Guangzhou, China. BPA exposure was assessed through urine samples using ultra-high performance liquid chromatography- tandem mass spectrometry, and body composition parameters were measured through bioelectrical impedance analysis (InBody770). Results: The median urinary BPA concentration was 0.556 μg/L (IQR: 0.301 - 1.031 μg/L) and creatinine-adjusted BPA concentration was 0.930 μg/g (IQR: 0.551 - 1.586 μg/g). BPA levels were significantly associated with body mass index (β= 1.15; 95%CI: 0.47, 1.83), body fat mass (β= 1.14; 95%CI: 0.39, 1.89), fat free mass (β= 0.92; 95%CI: 0.26, 1.58), and percent body fat (β= 3.44; 95%CI: 1.17, 5.71) after adjusting for potential confounding factors. Similarly, adjusted models with log10-transformed creatinine-adjusted BPA concentrations as a continuous variable showed similar trends. Positive linear associations were observed between quartiles of BPA concentrations and body composition parameters, with the highest coefficients in the fourth quartile. Conclusions: Our study provides further evidence of positive correlations between BPA exposure and body composition parameters in children aged 4 to 6 years. These findings highlight the potential health risks associated with obesity-related body composition parameters in young children. Further investigations are needed to confirm this association and explore the underlying mechanisms.